Low lithium loss high temperature resistant gamma-Li2TiO3 ceramic pellets and method of making same

CN123003275APending Publication Date: 2026-10-30XIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611430202.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种低锂损失耐高温的γ-Li2TiO3陶瓷小球及其制备方法,用以解决现有Li2TiO3在烧结和制备过程中锂的汽化挥发现象严重且热稳定性较差的技术问题

Benefits of technology

本发明公开了一种低锂损失耐高温的γ-Li2TiO3陶瓷小球的制备方法,该方法首先以Li2CO3、TiO2、MgO和Ta2O5为原料制备γ-Li2TiO3纳米粉体,实现在Li2TiO3中引入Mg2+和Ta5+复合离子替代Ti4+,从粉体合成阶段即降低β→γ相变能垒,使得本需1155℃以上才能发生的β→γ相变在750~800℃的煅烧温度下即可完成,从而在粉体层面获得高温稳定的γ-Li2TiO3,奠定了高温结构稳定性的基础;随后将γ-Li2TiO3纳米粉体制备成陶瓷小球生坯,其作用在于将已具备立方相结构优势的粉体无损地成型为小球形态,避免了成型工艺中相变回β相或引入额外缺陷的风险,确保了步骤1的晶体结构优势在生坯阶段得以完整保留;最后通过对生坯进行烧结,其作用在于在远低于β→γ相变温度(1155℃)的条件下直接烧结得到立方相γ-Li2TiO3陶瓷小球。本发明的方法使得γ相在粉体合成阶段即已获得,烧结仅需在相对温和的条件下完成致密化,从而打破了γ相转变需高温与锂挥发随高温加剧之间的矛盾,使两者不再互为制约,实现了极低的锂损失率和优异的高温结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003275A_ABST
    Figure CN123003275A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low lithium loss high-temperature-resistant gamma-Li2TiO3 ceramic small balls and preparation method thereof, belong to solid-state tritium breeding material technical field.The method disclosed in the application prepares gamma-Li2TiO3 Nano powder with Li2CO3, TiO2, MgO and Ta2O5 as raw materials, realizes the introduction of Mg 2+ And Ta 5+ Composite ion replaces Ti 4+ Subsequently, gamma-Li2TiO3 Nano powder is prepared into ceramic small ball green body, finally by sintering to green body.The method makes gamma phase obtain in powder synthesis stage, and sintering is only needed to complete densification under relatively mild conditions, so as to break the contradiction between high temperature required for gamma phase transformation and lithium volatilization intensified with high temperature, so that they are no longer mutual restriction, realize extremely low lithium loss rate and excellent high-temperature structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid tritium breeding materials technology, specifically relating to a low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microsphere and its preparation method. Background Technology

[0002] As a key functional material in the blanket of a fusion reactor, tritium breeder can react with neutrons to generate tritium, enabling fuel self-sufficiency in the fusion reactor. To achieve tritium self-sufficiency and steady-state operation of the fusion reactor, the tritium breeder must have a high tritium breeding ratio (TBR>1), which mainly depends on the lithium atom density of the breeder (generally, the higher the lithium atom density, the higher the tritium breeding ratio). Lithium titanate (Li₂TiO₃) is widely recognized as one of the most promising solid-state tritium breeder materials due to its good chemical stability, moderate thermal conductivity, and excellent tritium release performance.

[0003] However, a major drawback of lithium titanate is the severe lithium volatilization that occurs during sintering and high-temperature service, significantly reducing the lithium atom density and consequently the tritium breeding ratio (TBR). Studies have shown that β-Li₂TiO₃ (monoclinic phase) has a layered structure consisting of alternating pure Li and LiTi₂ layers. The Li atoms in the (002) crystal plane are highly reactive, easily generating vacancies, substitutions, and defects. These intrinsic structural defects are the fundamental reason for the severe lithium vaporization during sintering and service of β-Li₂TiO₃. Notably, the β→γ phase transition temperature is as high as 1155 °C, making it difficult to obtain highly stable γ-Li₂TiO₃ (cubic phase) at lower sintering temperatures. Therefore, suppressing lithium volatilization during preparation, sintering, and service is an important development direction in the field of lithium titanate tritium breeding ceramics.

[0004] Currently, the main technical approach to solving the lithium volatilization problem is to add lithium-rich phases to compensate for lithium loss. This involves adding an excess of lithium-containing phases (such as LiO2, Li2CO3, LiF, etc.) during the preparation of lithium titanate to compensate for lithium loss during sintering and high-temperature processes. However, the added lithium-containing phases typically have low melting points, preferentially melting and segregating at grain boundaries, reducing grain boundary strength. Simultaneously, problems such as Ostwald ripening occur, causing abnormal grain growth and affecting tritium release efficiency. One literature (Gong Y, Na Q, Dang C, et al. Enhancing the density and crush load of Li2TiO3 tritium breedingceramic pebbles by adding LiNO3-Li2CO3[J]. Annals of Nuclear Energy, 2024,196: 110251.) suggests that adding 5 wt% lithium nitrate and lithium carbonate can compensate for lithium loss during sintering. The pebbles sintered at 750 °C exhibit high mechanical strength, but still face significant lithium volatilization and poor structural stability issues when approaching the fusion reactor service temperature limit (900 °C). Another technical approach to address lithium volatilization is to composite high-lithium-content tritium breeding materials (such as Li4SiO4 and Li4TiO4) with Li2TiO3 to improve the overall lithium density. The literature (Rao GJ, Mazumder R, Bhattacharyya S, et al. Fabrication and characterization of Li4SiO4-Li2TiO3 composite ceramic pebbles using extrusion and spherodization technique[J]. Journal of the European Ceramic Society, 2018, 38(15): 5174-5183.) prepared uniformly distributed biphase Li4SiO4-Li2TiO3 ceramics by a rolling method to improve mechanical strength and lithium density. However, due to the significant differences in crystal structure and physicochemical properties between Li4SiO4 and Li2TiO3, the phase boundary bonding strength is low during service, leading to interfacial debonding. At high temperatures, due to the difference in thermal conductivity and coefficient of thermal expansion, cracks preferentially initiate at the phase boundary, causing material cracking.

[0005] None of the aforementioned technical solutions fundamentally solve the problem of lithium volatilization at high temperatures, because they fail to alter the layered crystal structure of β-Li₂TiO₃. Therefore, addressing lithium volatilization at the crystal structure level while simultaneously ensuring high-temperature thermal stability is a critical technical challenge that urgently needs to be overcome in this field. Summary of the Invention

[0006] The purpose of this invention is to provide a low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microsphere and its preparation method, in order to solve the technical problems of severe lithium vaporization and volatilization and poor thermal stability in existing Li2TiO3 during sintering and preparation processes.

[0007] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres, comprising the following steps: S1: γ-Li₂TiO₃ nanoparticles were prepared using Li₂CO₃, TiO₂, MgO, and Ta₂O₅ as raw materials via a solid-state method; during this preparation process, MgO and Ta₂O₅ contained Mg... 2+ and Ta 5+ Formation (Mg) 1 / 3 Ta 2 / 3 ) 4+ A composite ion that replaces Ti in Li₂TiO₃ 4+ The molar amount of Ti sites replaced is 30% to 40%; S2: Using γ-Li2TiO3 nanopowder and ethylene glycol solution as raw materials, γ-Li2TiO3 ceramic microsphere green bodies with low lithium loss and high temperature resistance were prepared; S3: After sintering the green body of γ-Li2TiO3 ceramic microspheres with low lithium loss and high temperature resistance, γ-Li2TiO3 ceramic microspheres with low lithium loss and high temperature resistance are obtained.

[0008] Furthermore, in S1, the specific steps for preparing γ-Li2TiO3 nanopowder are as follows: S11: Li2CO3, TiO2, MgO and Ta2O5 were placed in a nylon ball milling jar, zirconium oxide balls were added, and then anhydrous ethanol was added for ball milling to obtain the ball milling product; S12: After drying, grinding and calcining the ball-milled product in sequence, γ-Li2TiO3 powder is obtained; S13: After grinding the γ-Li2TiO3 powder, put it into a carbide ball mill jar, add carbide balls and anhydrous ethanol, and then put it into a high-energy ball mill for ball milling. S14: The obtained ball-milled product was dried and ground to obtain γ-Li2TiO3 nanopowder.

[0009] Furthermore, in S11, the molar ratio of Li2CO3, TiO2, MgO, and Ta2O5 is 1.1:(0.6~0.7):(0.1~0.13):(0.1~0.13). The zirconium oxide balls are added at a ball-to-material ratio of 5:1 to 10:1; the amount of anhydrous ethanol added is 50 to 70 mL.

[0010] Furthermore, in S12, the drying temperature is 80~100 ℃ and the time is 10~12 h; The calcination treatment is carried out at a temperature of 750 ℃ ​​to 800 ℃ for a time of 2 to 6 hours.

[0011] Further, in S13, for every 20 g of γ-Li2TiO3 powder, carbide balls are added at a ball-to-powder ratio of 10:1 to 20:1, followed by the addition of 50 to 70 mL of anhydrous ethanol; the ball milling process is carried out at a speed of 180 to 200 rpm for 12 to 24 h, with a 10 min break after every 1 to 2 h of ball milling. In S14, the drying temperature is 70~100 ℃ and the time is 10~12 h.

[0012] Furthermore, in S2, the specific steps for preparing the γ-Li2TiO3 ceramic microsphere green body are as follows: S21: Add γ-Li2TiO3 nanoparticles to an ethylene glycol solution to obtain a slurry; S22: The slurry is dropped into liquid nitrogen to form small balls. Finally, the small balls are removed from the liquid nitrogen and dried to obtain γ-Li2TiO3 ceramic small ball green bodies.

[0013] 7. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 6, characterized in that, in step S21, the concentration of the ethylene glycol solution is 20 vol%; and the solid content of the slurry is 45-55 wt%. In S22, the dripping rate is 10-20 drops / minute, and the volume of each drop is 0.9-1.7 mm. 3 The method for removing the small balls from liquid nitrogen and drying them is as follows: place the small balls on filter paper to air dry, and then transfer them to a constant temperature drying oven at 70 ℃~100 ℃ for 12~24 h.

[0014] Furthermore, in S3, the sintering treatment temperature is 900 ℃~1100 ℃, and the time is 2~6 h.

[0015] The present invention also discloses a low-lithium-loss, high-temperature resistant γ-Li2TiO3 ceramic microsphere prepared by the above preparation method.

[0016] Furthermore, the low-lithium-loss, high-temperature resistant γ-Li2TiO3 ceramic microspheres have a grain size of 1.85 μm, a density of 83%~87%, a crushing load of 52~110 N, and a lithium mass loss rate of no more than 0.26% after being kept at 900 ℃ for 100 h.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres. The method first prepares γ-Li₂TiO₃ nanopowder using Li₂CO₃, TiO₂, MgO, and Ta₂O₅ as raw materials, thereby introducing Mg into Li₂TiO₃. 2+ and Ta 5+ Composite ion substitution for Ti 4+ By lowering the β→γ phase transition energy barrier from the powder synthesis stage, the β→γ phase transition, which normally requires temperatures above 1155℃, can be completed at a calcination temperature of 750~800℃. This results in high-temperature stable γ-Li2TiO3 at the powder level, laying the foundation for high-temperature structural stability. Subsequently, the γ-Li2TiO3 nanoparticles are prepared into ceramic microsphere green bodies. This process allows the powder, which already possesses the advantages of a cubic phase structure, to be formed into microspheres without damage. This avoids the risk of phase transition back to the β phase or the introduction of additional defects during the forming process, ensuring that the crystal structure advantages of step 1 are fully preserved in the green body stage. Finally, the green bodies are sintered, which allows for direct sintering at temperatures far below the β→γ phase transition temperature (1155℃) to obtain cubic γ-Li2TiO3 ceramic microspheres. The method of this invention allows the γ phase to be obtained during the powder synthesis stage, and sintering only requires densification under relatively mild conditions. This breaks the contradiction between the high temperature required for γ phase transformation and the increased lithium volatilization with high temperature, so that the two no longer restrict each other, achieving extremely low lithium loss rate and excellent high-temperature structural stability. Attached Figure Description

[0018] Figure 1 The XRD patterns of the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres prepared in Examples 1 to 3 of this invention are shown below. Figure 2 The crushing load and density spectra of the low lithium loss, high temperature resistant γ-Li2TiO3 ceramic microspheres prepared in Examples 1 to 3 of this invention; Figure 3 EBSD image of the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres prepared in Example 1 of this invention; Figure 4 This is a cross-sectional SEM image of the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres prepared in Example 1 of this invention. Figure 5 The mass loss spectra of the low lithium loss, high temperature resistant γ-Li2TiO3 ceramic microspheres prepared in Examples 1 to 3 of this invention are obtained after being exposed to heat at 900℃ for 100 h. Detailed Implementation

[0019] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0021] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0022] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0023] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0024] To address the problems of severe lithium vaporization and poor thermal stability during the sintering and preparation of Li₂TiO₃, this invention provides a method for preparing γ-Li₂TiO₃ ceramic microspheres with low lithium loss and high temperature resistance up to 900℃. Specifically, by doping with heterogeneous elements, the phase transition energy barrier of Li₂TiO₃ is lowered, allowing the β-Li₂TiO₃ phase to transform into γ-Li₂TiO₃ with low lithium loss and a more stable high-temperature structure, thus obtaining γ-Li₂TiO₃ ceramics. Unlike existing technologies that "compensate" for lithium loss by adding lithium-rich phases or "sacrifice" interface integrity through composite design, this invention introduces composite ions (Mg²⁺, ... 2+ / Ta5+ Replace Ti 4+ This reduces the β→γ phase transition energy barrier of Li2TiO3 at the crystal structure level, allowing the high-temperature stable cubic phase γ-Li2TiO3 to exist stably at room temperature, thus fundamentally solving the lithium volatilization problem.

[0025] To achieve the above objectives, the basic concept of this invention is to introduce composite ions (Mg) into the Li₂TiO₃ lattice. 2 + / Ta 5+ Replace Ti 4+ The β→γ phase transition temperature of Li2TiO3 was lowered, and γ-Li2TiO3 ceramics were prepared by controlling the sintering temperature.

[0026] This invention discloses a method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres, comprising the following steps: Step 1: Prepare γ-Li₂TiO₃ nanopowder using an improved solid-state method; Step 1.1: Weigh Li₂CO₃, TiO₂, MgO, and Ta₂O₅ in a molar ratio of 1.1:0.7:0.1:0.1~1.1:0.6:0.13:0.13, wherein the MgO... 2+ and Ta 5+ With (Mg 1 / 3 Ta 2 / 3 ) 4+ Ti replaced by composite ions 4+ The substitution amount (molar amount) is 30%~40% of the Ti site. It is placed in a nylon ball milling jar, and zirconia balls are added at a ball-to-material ratio of 5:1~10:1. Then 50~70 mL of anhydrous ethanol is added. In this step, (Mg) 1 / 3 Ta 2 / 3 ) 4+ Composite ion substitution for Ti 4+ Subsequently, the formation of defects was reduced through synergistic charge compensation, and the local coordination environment of Ti sites and the bond length and bond angle of Ti-O bonds were adjusted, causing changes in crystal lattice distortion and stress distribution, and reducing the energy required for lattice reconstruction during the β-to-γ phase transition. Simultaneously, composite doping helps to reduce the free energy difference between the β and γ phases, thereby lowering the β→γ phase transition energy barrier and reducing the phase transition temperature. Step 1.2: Place the ball milling jar from Step 1.1 into a planetary ball mill for ball milling at a speed of 180-200 rpm for 6 hours, with a 10-minute break every 1-2 hours of ball milling. Step 1.3: Pour the ball milling product from Step 1.2 into a petri dish and dry it in a drying oven at 80~100 ℃ for 10~12 h; Step 1.4: Grind the dried powder from Step 1.3 and calcine it in a muffle furnace at 750 ℃~800 ℃ for 2~6 h to obtain γ-Li2TiO3 powder; Step 1.5: Grind the powder dried in Step 1.4, then weigh 20 g of the ground γ-Li2TiO3 powder, place it in a carbide ball mill jar, add carbide balls at a ball-to-material ratio of 10:1 to 20:1, and then pour in 50 to 70 mL of anhydrous ethanol. Step 1.6: Place the carbide ball milling jar from Step 1.5 into a high-energy ball mill for ball milling at a speed of 180-200 rpm for 12-24 hours, with a 10-minute break every 1-2 hours of ball milling. Step 1.7: Pour the ball milling product from Step 1.6 into a petri dish and dry it in a drying oven at 70~100 ℃ for 10~12 h. Then grind it to obtain γ-Li2TiO3 nanopowder. Step 2 is implemented in the following steps: Step 2.1: Prepare a 20 vol% ethylene glycol solution, and then add the γ-Li2TiO3 nanoparticles obtained in step 1.7 to make a slurry with a solid content of 45~55 wt%. Step 2.2: Drop the slurry obtained in step 2.1 into liquid nitrogen to form small balls. Finally, remove the small balls from the liquid nitrogen and dry them to obtain a green body of γ-Li2TiO3 ceramic small balls with low lithium loss and high temperature resistance.

[0027] In step 2.2, the slurry is added to liquid nitrogen at a rate of 10-20 drops / minute, with each drop having a volume of 0.9-1.7 mm. 3 .

[0028] In step 2.2, the method for removing and drying the small balls from liquid nitrogen is as follows: after air drying on filter paper, the small balls are transferred to a constant temperature drying oven at 70~100 ℃ and kept at that temperature for 12~24 h.

[0029] Step 3 is implemented in the following steps: The low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres obtained in step 2 are sintered at 900~1100 ℃ for 2~6 h, and then cooled to room temperature to obtain the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres.

[0030] The method of this invention introduces composite ions (Mg) into the Li₂TiO₃ lattice. 2 + / Ta 5+ Replace Ti 4+By lowering the β→γ phase transition temperature of Li₂TiO₃ and controlling the sintering temperature, γ-Li₂TiO₃ ceramics were prepared. Through composite ion doping, high-temperature resistant γ-Li₂TiO₃ ceramics with low lithium loss were successfully prepared. This solves the problem of balancing severe lithium loss with high-temperature structural stability in existing technologies.

[0031] The method of this invention does not add a low-melting-point lithium-rich phase, thus avoiding grain boundary weakening issues; it does not involve heterogeneous phase composites, eliminating interface debonding and crack initiation problems caused by differences in thermal expansion coefficients. The cubic γ-Li₂TiO₃ lacks the highly reactive (002) crystal plane of the β phase, resulting in higher binding energy of lithium atoms in the lattice. Therefore, lithium volatilization and loss during sintering and service are significantly improved. γ-Li₂TiO₃ is a high-temperature cubic phase, exhibiting excellent thermal stability within the tritium blanket service temperature range (300~900 °C) of fusion reactors. This invention stabilizes the γ phase to room temperature while retaining its high-temperature structural characteristics through doping, enabling the ceramic microspheres to maintain good structural and performance stability during long-term high-temperature service in fusion reactors. This solves the problem of severe lithium loss and difficulty in achieving high-temperature structural stability in existing technologies.

[0032] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0033] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0034] Example 1 A method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres includes the following steps: (1) Preparation of γ-Li2TiO3 nanopowder The molar ratio of Li₂CO₃, TiO₂, MgO, and Ta₂O₅ was weighed as 1.1:0.7:0.1:0.1, wherein the Mg... 2+ and Ta 5+ With (Mg 1 / 3 Ta 2 / 3 ) 4+Ti replaced by composite ions 4+ The substitution amount (molar amount) was 30% of the Ti site. The mixture was placed in a nylon ball mill jar, and zirconia balls with a ball-to-material ratio of 5:1 were added. 50 mL of alcohol was poured in. The ball mill jar was then placed in a ball mill and ball milled at 180 rpm for 6 h, with a 10 min break after every 1 h of ball milling. The ball milling product was poured into a petri dish and dried in a drying oven at 80 ℃ for 10 h. The dried powder was then ground and calcined in a muffle furnace at 750 ℃ ​​for 2 h to obtain γ-Li2TiO3 powder. The dried powder was ground, and 20g of γ-Li₂TiO₃ powder was weighed and added to carbide balls at a ball-to-powder ratio of 10:1. Then, 50 mL of anhydrous ethanol was poured in. The ball mill jar was then placed in a ball mill and milled at 180 rpm for 12 hours, with a 10-minute break after each hour of milling. The milled product was poured into a petri dish and dried in a drying oven at 80 ℃ for 10 hours. The dried product was then ground using an agate mortar and pestle to obtain γ-Li₂TiO₃ nanoparticles. (2) Preparation of γ-Li2TiO3 ceramic green bodies with low lithium loss and high temperature resistance; γ-Li₂TiO₃ nanoparticles were mixed with a self-made 20 vol% ethylene glycol aqueous solution in a certain proportion to prepare a slurry with a solid content of 45 wt%. The slurry was then dropped into liquid nitrogen at a rate of 10 drops / minute to form small spheres (each drop had a volume of approximately 0.9~1.7 mm). 3 Then, the small balls are removed from liquid nitrogen and placed on filter paper to air dry. After that, they are transferred to a 70℃ constant temperature forced air drying oven to dry for 12 h to obtain γ-Li2TiO3 ceramic small ball green bodies with low lithium loss and high temperature resistance. (3) Sintered γ-Li2TiO3 ceramics with low lithium loss and high temperature resistance The low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres obtained in step 2 were sintered in a sintering furnace at 900℃ for 2.5 hours. After sintering, they were cooled to room temperature with the furnace to obtain the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres.

[0035] The XRD pattern of the low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres prepared in Example 1 is shown below. Figure 1 EBSD, for example Figure 3 As shown, combined with Figure 1 and Figure 3 It can be seen that its main component is cubic phase Li₂TiO₃. Combined with... Figure 2 and Figure 4It can be seen that the density of the ceramic microsphere is 83.52%, the average crushing load is 52 N, and the grain size of the low-lithium-loss, high-temperature-resistant cubic Li₂TiO₃ phase is approximately 1.85 μm. Figure 5 The lithium loss of γ-Li₂TiO₃ ceramic after holding at 900 ℃ for 100 h can be observed. The graph shows a lithium loss rate of 8 × 10⁻⁶. -5 mg / (h·mm 2 ).

[0036] Example 2 A method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres includes the following steps: (1) Preparation of γ-Li2TiO3 nanopowder The molar ratio of Li₂CO₃, TiO₂, MgO, and Ta₂O₅ was weighed as 1.1:0.66:0.11:0.11, wherein the MgO... 2+ and Ta 5+ With (Mg 1 / 3 Ta 2 / 3 ) 4+ Ti replaced by composite ions 4+ The γ-Li₂TiO₃ powder was prepared by replacing 34% of the Ti sites in a nylon ball mill jar with zirconia balls at a ball-to-material ratio of 7:1. 62 mL of alcohol was added. The jar was then placed in a ball mill and milled at 190 rpm for 6 hours, with a 10-minute break after every 2 hours of milling. The milled product was poured into a petri dish and dried in a drying oven at 91 °C for 11 hours. The dried powder was then ground and calcined in a muffle furnace at 760 °C for 4.2 hours to obtain γ-Li₂TiO₃ powder. The dried powder was ground, and 20g of γ-Li₂TiO₃ powder was weighed and added to carbide balls at a ball-to-powder ratio of 16:1. Then, 60 mL of anhydrous ethanol was poured in. The ball mill jar was then placed in a ball mill and ball milled at 190 rpm for 18 h, with a 10 min break every 1.5 h. The ball-milled product was poured into a petri dish and dried in a drying oven at 80 ℃ for 10 h. The dried product was then ground in an agate mortar to obtain γ-Li₂TiO₃ nanopowder. (2) Preparation of γ-Li2TiO3 ceramic green bodies with low lithium loss and high temperature resistance; γ-Li₂TiO₃ nanoparticles were mixed with a self-made 20 vol% ethylene glycol aqueous solution in a certain proportion to prepare a slurry with a solid content of 51 wt%. The slurry was then dropped into liquid nitrogen at a rate of 15 drops / minute to form small spheres (each drop had a volume of approximately 0.9~1.7 mm). 3Then, the small balls are removed from liquid nitrogen, placed on filter paper to air dry, and then transferred to a 90 ℃ constant temperature forced air drying oven to dry for 16 h, thus obtaining a low lithium loss and high temperature resistant γ-Li2TiO3 ceramic small ball green body. (3) Sintered γ-Li2TiO3 ceramics with low lithium loss and high temperature resistance The low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres obtained in step 2 were sintered in a sintering furnace at 1000℃ for 4.5 hours. After sintering, the microspheres were cooled to room temperature with the furnace to obtain the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres.

[0037] The XRD pattern of the low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres prepared in Example 2 is shown below. Figure 1 It can be seen that its main component is cubic Li₂TiO₃. Combined with... Figure 2 It can be seen that the density of the ceramic microsphere is 86.03%, and the average crushing load is 67 N. Figure 5 The lithium loss of the γ-Li₂TiO₃ ceramic after holding at 900 ℃ for 100 h can be observed. The figure shows a lithium loss rate of 3 × 10⁻⁶. -5 mg / (h·mm 2 ).

[0038] Example 3 A method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres includes the following steps: (1) Preparation of γ-Li2TiO3 nanopowder The molar ratio of Li₂CO₃, TiO₂, MgO, and Ta₂O₅ was weighed as 1.1:0.6:0.13:0.13. The MgO... 2+ and Ta 5+ With (Mg 1 / 3 Ta 2 / 3 ) 4+ Ti replaced by composite ions 4+ The 40% Ti substitution was placed in a nylon ball mill jar, and zirconia balls with a ball-to-material ratio of 10:1 were added. 70 mL of alcohol was poured in. The ball mill jar was then placed in a ball mill and ball milled at 200 rpm for 6 h, with a 10 min break every 2 h. The ball milling product was poured into a petri dish and dried in a drying oven at 100 ℃ for 12 h. The dried powder was then ground and calcined in a muffle furnace at 800 ℃ for 6 h to obtain γ-Li2TiO3 powder. The dried powder was ground, and 20g of γ-Li₂TiO₃ powder was weighed and added to carbide balls at a ball-to-powder ratio of 20:1. Then, 70 mL of anhydrous ethanol was poured in. The ball mill jar was then placed in a ball mill and milled at 300 rpm for 24 hours, with a 10-minute break every 2 hours. The milled product was poured into a petri dish and dried in a drying oven at 100 °C for 12 hours. The dried product was then ground using an agate mortar and pestle to obtain γ-Li₂TiO₃ nanoparticles. (2) Preparation of γ-Li2TiO3 ceramic green bodies with low lithium loss and high temperature resistance; γ-Li₂TiO₃ nanoparticles were mixed with a self-made 20 vol% ethylene glycol aqueous solution in a certain proportion to prepare a slurry with a solid content of 55 wt%. The slurry was then dropped into liquid nitrogen at a rate of 20 drops / minute to form small spheres (each drop approximately 0.9~1.7 mm in volume). 3 Then, the small balls are removed from liquid nitrogen, placed on filter paper to air dry, and then transferred to a 100 ℃ constant temperature forced air drying oven to dry for 24 h, thus obtaining a low lithium loss and high temperature resistant γ-Li2TiO3 ceramic small ball green body. (3) Sintered γ-Li2TiO3 ceramics with low lithium loss and high temperature resistance The low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres obtained in step 2 were sintered in a sintering furnace at 1100 ℃ for 6 h. After sintering, the microspheres were cooled to room temperature in the furnace to obtain the low-lithium-loss, high-temperature-resistant γ-Li2TiO3 ceramic microspheres.

[0039] The XRD pattern of the low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres prepared in Example 3 is shown below. Figure 1 It can be seen that its main component is cubic Li₂TiO₃. Combined with... Figure 3 It can be seen that the density of the ceramic microsphere is 86.12%, and the average crushing load is 105 N. Figure 5 The lithium loss of the γ-Li₂TiO₃ ceramic after holding at 900 ℃ for 100 h can be observed. The figure shows a lithium loss rate of 4 × 10⁻⁶. -4 g / (h·mm 2 ).

[0040] contrast Figures 2-5 It can be clearly seen that, by using composite ions (Mg...) 2+ / Ta 5+ Replace Ti 4+ This process was used to promote the synthesis of γ-Li₂TiO₃ and ensure the stability of the cubic phase at room temperature. The synthesized low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres had a grain size of approximately 1.85 μm, and the crushing load met the requirements for fusion reactors. After a 100-hour lithium volatilization rate test, from... Figure 5 From this, it can be concluded that the lithium loss rate of β-Li₂TiO₃ is 8 × 10⁻⁶. -4 mg / (h·mm 2 The lithium mass loss was approximately 3.09%; the prepared low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ showed a lithium loss rate of 8 × 10⁻⁶. -5 mg / (h·mm 2 The lithium mass loss is approximately 0.26%, representing an order of magnitude increase in the lithium loss rate. Furthermore, the sintering temperature is 90–110°C, ensuring long-term safe operation within the fusion reactor's temperature range of 300–900°C.

[0041] Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention. For example, through other oxygen ions (such as Pb...) 4+ Zr 4+ 、Nb 5+ Cubic Li2TiO3 and its multiphase tritium breeding materials (β-Li2TiO3 / γ-Li2TiO3, γ-Li2TiO3 / lithium orthosilicate, γ-Li2TiO3 / lithium zirconate and other multiphase ceramics) prepared by doping (etc.).

[0042] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres, characterized in that, Includes the following steps: S1: γ-Li₂TiO₃ nanopowder was prepared by solid-state method using Li₂CO₃, TiO₂, MgO, and Ta₂O₅ as raw materials; during this preparation process, MgO and Ta₂O₅ contained Mg... 2+ and Ta 5+ Formation (Mg) 1 / 3 Ta 2 / 3 ) 4+ A composite ion that replaces Ti in Li₂TiO₃ 4+ The molar amount of Ti sites replaced is 30% to 40%; S2: Using γ-Li2TiO3 nanopowder and ethylene glycol solution as raw materials, γ-Li2TiO3 ceramic microsphere green bodies with low lithium loss and high temperature resistance were prepared; S3: After sintering the green body of γ-Li2TiO3 ceramic microspheres with low lithium loss and high temperature resistance, γ-Li2TiO3 ceramic microspheres with low lithium loss and high temperature resistance are obtained.

2. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 1, characterized in that, In S1, the specific steps for preparing γ-Li2TiO3 nanopowder are as follows: S11: Li2CO3, TiO2, MgO and Ta2O5 were placed in a nylon ball milling jar, zirconium oxide balls were added, and then anhydrous ethanol was added for ball milling to obtain the ball milling product; S12: After drying, grinding and calcining the ball-milled product in sequence, γ-Li2TiO3 powder is obtained; S13: After grinding the γ-Li2TiO3 powder, put it into a carbide ball mill jar, add carbide balls and anhydrous ethanol, and then put it into a high-energy ball mill for ball milling. S14: The obtained ball-milled product was dried and ground to obtain γ-Li2TiO3 nanopowder.

3. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 2, characterized in that, In S11, the molar ratio of Li2CO3, TiO2, MgO and Ta2O5 is 1.1:(0.6~0.7):(0.1~0.13):(0.1~0.13). The zirconium oxide balls are added at a ball-to-material ratio of 5:1 to 10:1; the amount of anhydrous ethanol added is 50 to 70 mL.

4. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 2, characterized in that, In S12, the drying temperature is 80~100 ℃ and the time is 10~12 h; The calcination treatment is carried out at a temperature of 750 ℃ ​​to 800 ℃ for a time of 2 to 6 hours.

5. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 2, characterized in that, In S13, for every 20 g of γ-Li2TiO3 powder, carbide balls are added at a ball-to-powder ratio of 10:1 to 20:1, followed by the addition of 50 to 70 mL of anhydrous ethanol; the ball milling process is carried out at a speed of 180 to 200 rpm for 12 to 24 h, with a 10 min break after every 1 to 2 h of ball milling. In S14, the drying temperature is 70~100 ℃ and the time is 10~12 h.

6. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 1, characterized in that, In S2, the specific steps for preparing γ-Li2TiO3 ceramic microsphere green bodies are as follows: S21: Add γ-Li2TiO3 nanoparticles to an ethylene glycol solution to obtain a slurry; S22: The slurry is dropped into liquid nitrogen to form small balls. Finally, the small balls are removed from the liquid nitrogen and dried to obtain γ-Li2TiO3 ceramic small ball green bodies.

7. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 6, characterized in that, In S21, the concentration of the ethylene glycol solution is 20 vol%; the solid content of the slurry is 45-55 wt%. In S22, the dripping rate is 10-20 drops / minute, and the volume of each drop is 0.9-1.7 mm. 3 The method for removing the small balls from liquid nitrogen and drying them is as follows: place the small balls on filter paper to air dry, and then transfer them to a constant temperature drying oven at 70 ℃~100 ℃ for 12~24 hours.

8. The method for preparing low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microspheres according to claim 1, characterized in that, In S3, the sintering temperature is 900 ℃~1100 ℃ and the time is 2~6 h.

9. A low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microsphere, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.

10. A low-lithium-loss, high-temperature-resistant γ-Li₂TiO₃ ceramic microsphere according to claim 9, characterized in that, The low-lithium-loss, high-temperature resistant γ-Li2TiO3 ceramic microspheres have a grain size of 1.85 μm, a density of 83%~87%, a crushing load of 52~110 N, and a lithium mass loss rate of no more than 0.26% after being kept at 900 ℃ for 100 h.